Soil Organic Carbon and Total Nitrogen Stock Response to Traditional Enclosure Management in Eastern Ethiopia - Abdulahi, Mohammed; Ebro, Abule; Nigatu, Lisanework (International Livestock Research Institute, 2021)
Traditional enclosures are widely used by pastoralists in East Africa. However, the response of basic soil properties to the establishment of traditional enclosure management remains poorly understood. The aim of this study was to investigate the impacts of traditional enclosure on soil organic carbon and total nitrogen stock in the Bordade rangelands, eastern Ethiopia. Soil samples were collected from twelve area enclosures and openly grazed areas at a depth of 0-30 cm. The samples were analyzed for soil organic carbon, total nitrogen and bulk density. There were significant differences between enclosure and openly grazed areas in soil organic carbon and total nitrogen stock. Enclosures had significantly more 27.5% soil organic carbon and 27.5% total nitrogen stock compared with the area outside area enclosure. Overall, the study showed that establishment of rangeland enclosures and the short-term resting period followed by dry season grazing at light stocking rate has the potential to improve soil organic carbon and total nitrogen stock, which is an option for realizing positive vegetation changes that support the local pastoral economy in the semiarid rangelands of eastern Ethiopia.